IMPROVING FORAGE YIELD AND MORPHOLOGY OF OAT VARIETIES THROUGH VARIOUS ROW SPACING AND NITROGEN APPLICATION - M. Irfan; M. Ansar; A. Sher; A. Wasaya; A. Sattar (Journal of Animal and Plant Sciences, 2016)
Oat is winter season forage crop cultivated throughout the country. It is a fast growing, palatable, succulent and nutritious fodder crop. In this frame, two years field study was carried out at PMAS- Arid Agriculture University Rawalpindi, Pakistan during 2011-12 and 2012-13. It is hypothesized that row spacing and nitrogen (N) application improves morphology and yield forage production of oat varieties. Experiment comprised of four oat varieties (PD2-LV65, S-2000, NZ0034 and NARC-11) grown under each three N levels (60, 90 and 120 kg haˉ1) with row spacing of 12, 24 and 46 cm. Results revealed that var. PD2-LV65 was found more efficient with respect to plant height, number of leaves, biomass traits, green forage yield, dry matter yield and dry matter content than other tested varieties. The highest N rate (120 kg haˉ1) significantly affected above parameters than low level (60 kg N haˉ1). Higher morphological characters were recorded at 46 cm row spacing while maximum forage yield in narrow row spacing of 12 cm. From these results, we can conclude that var. PD2-LV65 perform better than all the other oat varieties and N application of 120 kg haˉ1 gave maximum morphological traits and forage yield but row spacing show variable behavior under sub-tropical conditions.
Keywords: Oat varieties; Nitrogen; Row spacing; Forage yield; sub-tropical conditions